FOLLOWING THE TRADITIONS OF THE BEDILI STYLE IN THE MODERN TAJIK POETRY OF UZBEKISTAN (in the example of Jaafar Muhammad Tirmidhi's poem) (Scientific journal of the Fergana State University, 2023)
The article is about the study of the continuation of the traditions of the Indian or Bedili style in modern Tajik literature, especially in the Tajik poetry of Uzbekistan. This topic is studied based on the analysis of some samples of Jaafar Muhammad Tirmidhi's ghazals. By the way, the poems of some Tajikistan poets are looked at from this point of view.